Swedish intensivists' experiences and attitudes regarding end‐of‐life decisions. Issue 5 (29th January 2020) - Nordenskjöld Syrous, Alma; Ågård, Anders; Kock Redfors, Maria; Naredi, Silvana; Block, Linda
Abstract : Background: To make end‐of‐life (EOL) decisions is a complex and challenging task for intensive care physicians and a substantial variability in this process has been previously reported. However, a deeper understanding of intensivists' experiences and attitudes regarding the decision‐making process is still, to a large extent, lacking. The primary aim of this study was to address Swedish intensivists' experiences, beliefs and attitudes regarding decision‐making pertaining to EOL decisions. Second, we aimed to identify underlying factors that may contribute to variability in the decision‐making process. Method: This is a descriptive, qualitative study. Semi‐structured interviews with nineteen intensivists from five different Swedish hospitals, with different ICU levels, were performed from 1 February 2017 to 31 May 2017. Results: Intensivists strive to make end‐of‐life decisions that are well‐grounded, based on sufficient information. Consensus with the patient, family and other physicians is important. Concurrently, decisions that are made with scarce information or uncertain medical prognosis, decisions made during on‐call hours and without support from senior consultants cause concern for many intensivists. Underlying factors that contribute to the variability in decision‐making are lack of continuity among senior intensivists, lack of needed support during on‐call hours and disagreements with physicians from other specialties. There is also an individual variability primarily depending on the intensivist's personality. Conclusion: Swedish intensivists' wish to make end‐of‐life decisions based on sufficient information, medically certain prognosis and consensus with the patient, family, staff and other physicians. Swedish intensivists' experience a variability in end‐of‐life decisions, which is generally accepted and not questioned.